La resolución de problemas de cantidad en estudiantes de segundo grado de secundaria en las Instituciones Educativas de San Juan Bautista según turno 2020 - Upiachihuay Rios, Luis Alberto (2024)
The objective of the research was to compare the achievement in solving quantity problems between the morning and afternoon shift in second grade secondary school students in the educational institutions of the district of San Juan Bautista according to the 2020 shift, the study was comparative. and field, contemporary transectional and univariate designs. The population was made up of 1149 students, we worked with a sample of 146 students from the morning shift and 144 students from the afternoon shift. The results show that the students in the morning shift obtained a higher average than the students in the afternoon shift in achievement of solving quantity problems (14.02 > 13.92). Just as in the indicators: translates quantities (17.15 >16.68), communicates its understanding (16.00> 15.28), the results show the opposite in the indicators, uses strategies and procedures (11.92<12 .92), argues statements (10.68<11.14). In conclusion, according to the Mann-Whitney U test for our independents, there is no significant difference in the students' achievement in solving quantity problems between the morning and afternoon shift (p-value >α = 0.05 )